Impact of fluoroquinolone treatment on delay of tuberculosis diagnosis: A systematic review and meta-analysis. (January 2017) - Hogan, Catherine A; Puri, Lekha; Gore, Genevieve; Pai, Madhukar
Abstract: Background: Fluoroquinolones are among the most commonly used antibiotics for the treatment of respiratory infections. Because fluoroquinolones show bactericidal activity against Mycobacterium tuberculosis, there is concern that their use can delay the diagnosis of tuberculosis. We conducted a systematic review and meta-analysis to assess whether empiric treatment with fluoroquinolones delays the diagnosis and treatment of tuberculosis in patients with respiratory tract infections. Objectives: The primary objective was to assess the delay in days in the diagnosis and treatment of tuberculosis, among patients who received quinolones, compared to those who received non-fluoroquinolone antibiotics. Methods: We included studies of adult patients treated with fluoroquinolones prior to a confirmed diagnosis of tuberculosis. We performed a literature search of 7 databases (including PubMed, Embase and Cochrane Library) with no language restrictions. We calculated an unweighted mean of estimate of difference in delay across all studies. For the studies for which the estimate was available as a mean with standard deviation, a weighted average using a random effects meta-analysis model was estimated. Results: A total of 3983 citations were identified from the literature search; of these, 17 articles were selected for full-text review. A total of 10 studies were retained for the synthesis. These included 7 retrospective cohort studies and 3 case-control studies. Only one of these studies was from a high TB burden country, South Africa. The most commonly used fluoroquinolones were levofloxacin, gemifloxacin and moxifloxacin. The unweighted average of difference in delay between the fluoroquinolone group and non-fluoroquinolone group was 12.9 days (95% CI 6.1–19.7). When these differences were pooled using a random effects model, the weighted estimate was 10.9 days (95% CI 4.2–17.6). When stratified by acid-fast smear status, the delay was consistently greater in the smear-negative group. Conclusion: Although results are variable, the use of fluoroquinolones in patients with respiratory infections seems to delay the diagnosis of TB by nearly two weeks. Consistent with the International Standards for TB Care, their use should be avoided when tuberculosis is suspected.